The Influence of Counseling Guidance and Spiritual Intelligence in Developing Students' Islamic Personality - Arizka Harisa (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2019)
This study aims to obtain information and to analyze the efforts in developing students' Islamic personality through counseling guidance and spiritual intelligence. The participants of the study are the teachers of Senior High Schools (SMAN) in Ciputat, South Tangerang. The data were collected by using correlation and regression analysis concerning the three research variables. From the result of this study, it was found that counseling guidance and spiritual intelligence had a significant correlation to the efforts of developing students’ Islamic personality in school. The role of the teachers in counseling guidance and spiritual intelligence towards students would be able to provide direction and enlightenment in students to have a good self-quality, based on the teachings in their religion. Therefore, the development of students' Islamic personality is one of the efforts carried out in preventing negative influences on students, so that it can make students have high personality qualities based on the values taught in religious teachings, in the hope of giving changes to student's quality in achieving student achievement in school.